Development of a Web-Based E-Complaint Platform with WebSocket Integration Using the Prototyping Method - Saputra, Jeki Adi; Sutopo, Joko (Yayasan Kita Menulis, 2025)
Manual handling of public complaints often results in delayed responses, lack of transparency, and limited feedback. This study aims to develop a web-based E-Complaint platform integrated with WebSocket technology to support real-time notifications, thereby improving the efficiency and accountability of public services. The research method used a prototyping approach, which included the stages of requirements gathering, system design, prototype development, and functional evaluation with users. The system implementation included complaint reporting, status tracking, administrator dashboard, and WebSocket-based instant notification channels when the report status changed. Functional testing results show that all main processes run according to user needs, the system responds quickly without significant delays, and communication between users and administrators is more efficient than manual processes. WebSocket integration has proven to increase the speed of information delivery and transparency in handling public complaints. Going forward, system development will focus on improving analytical features and optimizing web-based service performance